Humanoid Robot Technology and Industry Development - Chenghao Xu; Yaonan Wang; Yang Mo; Qing Zhu (中国工程科学)
With the continuous breakthroughs in technologies such as artificial intelligence, advanced manufacturing, and new materials, China's humanoid robot industry is experiencing explosive growth. Technological innovation and supportive policies have fostered a diversified and competitive landscape. However, China's humanoid robot industry still faces significant challenges, including lagging core technologies, high difficulty in mass production, and obstacles to commercialization. This study explores the major subfields and technological frontiers of humanoid robotics, offering an in-depth analysis of global trends in policies, technologies, and industrial development. It examines the current state of humanoid robotics in China and identifies key opportunities and challenges. Furthermore, the study proposes strategic recommendations to address these challenges, focusing on technological innovation, pilot demonstration, improvement in laws and regulations, and policy support. Specifically, the research recommends encouraging breakthroughs in core technologies, strengthening industrial layout, building humanoid robot infrastructure, and implementing demonstrative projects. These efforts aim to help China's humanoid robot industry overcome technical challenges, improve its industrial ecosystem, and achieve large-scale production and commercialization, thereby enhancing the global competitiveness of the industry.